Disassembly system design and analysis with environmental and economic parts selection using life cycle inventory database by input-output tables. (30th July 2021) - Yamada, Tetsuo; Suzuki, Yusuke; Kinoshita, Yuki; Masui, Tadayuki; Itsubo, Norihiro; Inoue, Masato
To prevent material starvation and global warming caused by manufacturing, disassembly systems for end-of-life (EOL) products should be environmentally and economically designed to promote a closed-loop supply chain for assembly products. With parts selection in the disassembly systems, parts/materials with higher CO2 volumes should be recycled for environmental reasons. On the other hand, parts/materials with higher profit, which is the difference between the revenue of recovered materials and disassembly costs, should be disassembled for economic reasons. A disassembly system design considering not only the environmental loads but also the recovered parts/materials is proposed by using a product lifecycle management (PLM) tool. However, from a technical and financial standpoint, it is not easy for the disassembly factory sites to create the 3D-CAD models and obtain the environmental information using the PLM tool. This paper proposes a disassembly system design with the environmental and economic parts selection using a life cycle inventory database by input-output tables.